Conjunctive use management strategy with small aquifers to minimize dry-season damage and meet instream flow targets - Cho, Young-Dae, author; Grigg, Neil S., advisor (Colorado State University. Libraries, 2008)
This dissertation addresses the connections between surface and ground water when alluvial aquifer systems are small, presents a series of technical and institutional analyses to show how to manage a limited water source at the basin level, and addresses management strategies for conjunctive use to understand and provide potential solutions for water conflicts. In the case study area, the middle section of the Geum River in Korea, the major issue is increasing in-stream flow requirements during severe drought that have been imposed by downstream stakeholders and nongovernmental organizations (NGO) after dam completion. The case also involves a large trans-basin diversion.

The technical analysis includes reviews of connectivity between surface and ground waters, development of response coefficients due to pumping wells, in-stream flow requirements, and conjunctive use approaches. The institutional analysis includes reviews of water right systems, organization, in-stream flow requirements, and data management to provide comparative perspectives.

Most alluvial aquifers along the main rivers in the case study area are relatively narrow and small. These aquifers are highly interconnected with the adjacent streams and the critical time to reverse the hydraulic gradients in the gaining streams is relatively short. The ratio of groundwater recharge to average annual precipitation is about 20%. The recharge occurs mostly in the rainy season from June to September in the study area and ground-water recharge is strongly correlated with the precipitation. The response coefficients of stream depletion due to the pumping wells are presented by using analytical and numerical methods.

In order to estimate the instream flow requirements, it is necessary to simulate the daily stream-flow at an ungaged site so that a rainfall-runoff model can be used to simulate the reservoir operation by using a standard operating policy. A simulated daily data set is used for analyzing the hydrologic alterations before and after the dam completion. Under the given conditions, the Yongdam Reservoir in the Geum River Basin highly impacts the hydrologic alterations. The main factor of hydrologic alteration is trans-basin water supply.In order to meet the water supply and downstream in-stream flow requirements for fish and aquatic habitat and minimize hydrologic alterations, the downstream in-stream flow requirement obtained by the method was determined to be about 3m/s based on the simulated data alteration.

In order to evaluate conjunctive use strategies, a multi-objective linear optimization model was developed to consider trans-basin diversion, instream flow requirements for fish and aquatic habitat, and withdrawal of groundwater and surface waters for irrigation. The response coefficient of stream depletion was estimated using a numerical method for transient state and fixed multiple wells and was incorporated into the conjunctive use model. For reservoir operation, a hedging rule was used to ration deficits from various water demands during the drought periods. An optimization software package was used for running the mixed-integer linear model.

In the application of the model, the first step was performed to set the priority of water supply for trans-basin diversion, in-stream flow requirements, and irrigation water use. Then, the priorities of in-stream flow requirements, trans-basin diversion, and irrigation water uses were quantified. Effects of using both surface and ground waters are evident, even though the thickness of aquifers developed along a main stream is relatively thin.

If water managers and decision makers understand the connection between groundwater and surface water, water management for the limited water resources can be more effective and efficient. However, the connection between surface water and groundwater has been ignored in water policy in Korea and rivers and aquifers have been managed by separate institutions. This occurs due to the hidden attribute of groundwater, stream-flow domination, time frames for groundwater movement and response, and institutional separation of expertise and administration.

In the institutional arrangements, four elements are highlighted, including the water rights system, organization, instream flow requirements, and data management. Institutional arrangements in Korea are compared to a limited extent with those at the federal level and in two states of the United States, California and Colorado. The comparisons provide a perspective on appropriate institutional arrangements for conjunctive use in Korea.

For conjunctive management, gaps that occur include problems related to water allocation including conflict coordination systems, vagueness of legal status of current water use rights in water allocation law and institutions, unclear permit criteria, in-stream flow requirements, and shortage and inaccuracy of observed stream-flow and groundwater level data. Alternatives or options for Korea are presented such as organizational coordination in cooperating between agencies or creating river basin organizations, one permitting system including total water accounting, linking of water management plans, one permitting system, trigger or thresholds, management zones, and monitoring performance.

In conclusion, even though in Korea alluvial aquifers along main rivers are narrow, small and thin, surface and ground waters must be considered and managed as a single source in both technical and institutional aspects. It is hoped that this dissertation can contribute to the understanding of interactions between surface and ground waters in Korea, and with more understanding, water managers and regulators can find better paths to water management and that legislation about water management can recognize the interaction between surface and ground waters.
Keywords: aquifers; conjunctive use management; dry-season damage; instream flow; civil engineering